Synthesis and characterization of ion-imprinted polymer for determination of ionized calcium in human blood serum - Al-Maibd, Rafah Jasim Mohammed (2021)
Calcium (Ca) is a vital element in the human body as it maintains the integrity of the bone system and acts as regulatory ion. Total calcium (tCa) circulates the human body in different forms with only ionized calcium CiCa) is the physiology active fraction. Direct measurement oftCa in human serum remains the most common way of assessing calcium status in patients. The majority of clinical laboratories do not have iCa analysers but instead predict iCa from the tCa value measured in the lab. However, one of the pressing issues is the potential of underdiagnoses of Ca deficiency due to the false prediction of iCa. The adsorption properties of ion-imprinted polymers (lIPs) make them ideal for the selective removal of Calcium ions [Ca(II)] from human blood serum and the subsequent determination of iCa level. Ca(lI)-IIP was developed from two naturally formed biopolymers, cellulose and sodium alginate. The polymers were dissolved in co-solvent and casted into films, Ca(lI) ions were added to the polymer matrix using CaCh bath, the polymer films were cross-linked using Epichlorohydrin (ECH) and then the template Ca(H) ions were extracted using EDT A. The final CaCII)-HP was in the form of white, porous film with high selectivity to CaCH) ion. Taguchi method was utilized to determine the optimum adsorption conditions of the Ca(JI)-HP, the resulted optimum conditions were pH 5.9, initial concentration (50 mg/l), dosage (300 mg) and 90 min contact time. The effects of pH, dosage, initial concentration on the CaCTI)adsorption process were investigated. The kinetic study of CaCH) adsorption fitted well with the pseudo-first-order while, the adsorption isotherm is well fitted with Langmuir isotherm model.